Comparison of Vitamin and Mineral Usage Status of Patients Applying to Family Health Centres Before and After Covid - Mercan Yağız; Hatice Cakir (Journal of Medical Education and Family Medicine)
Objective: Our aim in this study was to determine how the coronavirus disease 2019 (COVID-19) pandemic affects the use of vitamins and minerals and to determine the level of vitamin and mineral use compared with that in the pre-COVID-19 period.Materials and Methods: Our study is a cross-sectional descriptive study and was conducted with 306 volunteer participants over the age of 18 who applied to three different family health centers (FHCs) in Erzincan city center between February and April 2023. A survey of 25 questions was prepared and administered to the participants.Results: In our study, regular vitamin and mineral use (20.6%) was found to be low, but the use approximately doubled in cases of illness (39.9%). Additionally, vitamin and mineral use during the COVID-19 pandemic (56.7%) was higher than the rate used while currently ill. The percentage of participants who said that they did not use vitamins or minerals without consulting their doctor was 75.2%. These participants again stated that it is necessary to check the blood levels of vitamins and minerals (77.4%) and that too much is harmful (81%). A total of 84.3% of the participants said that they expected vitamins and minerals to be prescribed by the doctor when they were sick. Those who used vitamins and minerals before and during the COVID-19 pandemic claimed that their use of vitamins and minerals increased in the post-COVID-19 period as well. In addition, the percentage of women who reported that the COVID-19 pandemic increased their use of vitamins and minerals was greater than that of men.Conclusion: In our study, the use rates of vitamins and minerals, which are known to have effects on many systems, especially the immune system, were low before the COVID-19 pandemic but increased during the postpandemic period. To improve health and maintain well-being, deficiencies in vitamins and minerals should be replaced, and patients should be more informed of these issues.